The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5ra18649h
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline dihydroazulene photoswitches

Abstract: A large selection of photochromic dihydroazulene (DHA) molecules incorporating various substituents at position 2 of the DHA core was prepared and investigated for their ability to form liquid crystalline phases. Incorporation of an octyloxy-substituted biphenyl substituent resulted in nematic phase behavior and it was possible to convert one such compound partly into its vinylheptafulvene (VHF) isomer upon irradiation with light when in the liquid crystalline phase. This conversion resulted in an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…108 The thermal lifetime of the metastable vinylheptafulvene (VHF) depends on substituents and medium it is embedded in and is usually in the minute to hours range. [515][516][517] The compound was not yet used in aqueous systems, but in liquid crystals, 518 polymer films, 519 in macrocycles, 520 rotaxanes, 521 for solar energy storage, 522,523 or to photocontrol emission properties. 515 Moreover, the DHA/VHF couple can be combined with further photochromic units to assemble multi-stage switches 404,[524][525][526][527] or with electrochemically active unit to achieve photoswitchable redox properties.…”
Section: Mixed Mechanismsmentioning
confidence: 99%
“…108 The thermal lifetime of the metastable vinylheptafulvene (VHF) depends on substituents and medium it is embedded in and is usually in the minute to hours range. [515][516][517] The compound was not yet used in aqueous systems, but in liquid crystals, 518 polymer films, 519 in macrocycles, 520 rotaxanes, 521 for solar energy storage, 522,523 or to photocontrol emission properties. 515 Moreover, the DHA/VHF couple can be combined with further photochromic units to assemble multi-stage switches 404,[524][525][526][527] or with electrochemically active unit to achieve photoswitchable redox properties.…”
Section: Mixed Mechanismsmentioning
confidence: 99%
“…Previously, we have reported that DHAs 3 and 4 , which are both substituted with biaryl units (Figure ), exhibit mesophases not far above room temperature . The core DHA structure is rod‐shaped, which is a desirable quality for forming the nematic phase.…”
Section: Introductionmentioning
confidence: 90%
“…The core DHA structure is rod‐shaped, which is a desirable quality for forming the nematic phase. In the nematic phase, full conversion to the VHF was not possible, but photolysis of 4 did result in annihilation of the defects and established a higher degree of order in the resulting mesophase when the VHF underwent ring closure back to 4 . Synthetic developments in DHA chemistry have allowed for the introduction of aromatic substituents at the 7‐position .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations